The Effectiveness of Self-Induced Unclassified Therapeutic Tremor for Decreasing Secondary Traumatic Stress among Social Workers - Widarsih, Rina Eko; Widyana, Rahma; Lailatusifah, Siti Noor Fatmah (Faculty of Psychology, Diponegoro University, 2021)
Secondary traumatic stress symptoms are marked by the emergence of traumatic memories experienced by otherpeople, rejection of the stimulus that triggers traumatic memories, and emotional turmoil. If left untreated, it maylower the quality of service and health of social workers. To lower secondary traumatic stress symptoms, it isnecessary to deliver psychological treatment that can be easily and independently done, is effective and cost-efficient, and universal. As such, Therapeutic Tremor Exercises through Self-Induction are consideredappropriate to respond to this need. This study aims to identify the effect of self-induced unclassified therapeutictremor exercises on reducing secondary traumatic stress levels. This study hypothesizes that there will bedifferences in secondary traumatic stress levels among social workers before and after samples are given self-induced therapeutic tremor exercises. Subjects consisted of female social workers (n = 5) who were indirectlyexposed to traumatic stories of victims for at least 2 hours a week. The study used a single-group pre-post designby comparing secondary trauma stress levels before and after the intervention. The intervention was a one-dayjoint training and 14-day independent training. Wilcoxon’s signed-rank test showed significant differences withZ = -2.023, p = .043, whereby secondary trauma stress levels prior to the intervention (M = 45.4) was higher thanafter the intervention (M = 26.2).